FACTORS AFFECTING TOURIST VISITS DURING THE COVID-19 PANDEMIC IN DURIAN AGRO-TOURISM - Donny Ivan Samuel Simatupang; Helena Tatcher Pakpahan; Rory Jun Yoyada S (Journal of Agriculture, 2023)
Durian agro-tourism is located in Purba Baringin Village, Pakkat District, Humbang Hasundutan Regency. Durian agro-tourism uses durian as a tourist attraction to attract tourists to visit Durian agro-tourism, not only durian that tourists consider visiting Durian agro-tourism but other aspects such as resources, promotions, facilities and infrastructure, institutions, and visitor satisfaction felt by visitors. The purpose of the study was to determine the factors that influence tourist visits to Durian agro-tourism. The method of determining the sample is by purposive sampling method, or it is done intentionally. The results obtained from this study are: 1) The influence of resource, promotion, institutional, and visitor satisfaction variables on tourist visits simultaneously is 0.087, and 0.913 is influenced by other models 2) The influence of resources, promotion, facilities, and infrastructure, institutional and satisfaction variables visitors to tourist visits partially are Resources 0.324, promotions -0.216, facilities and infrastructure -0.112, institutions -0.036, and visitor satisfaction -0.011.